Degradation Of Methylene Blue Using Molecularly Imprinted Iron (III) Oxide Prepared Via Hydrothermal Method - Ong, Hoay Yee (Universiti Sains Malaysia, 2018)
Molecularly imprinted hematite (α-Fe2O3) nanoparticles were synthesized by hydrothermal preparation method. The synthesis was carried out by using iron chloride (FeCl3.6H2O) and ammonium hydroxide (NH3.H2O) as the reactants and methylene blue as a structure-directing agent. The influence of reaction temperature and the presence of the structure-directing agent on the degree of crystallinity, morphology, microstructure and surface functional groups of the α-Fe2O3 samples were studies and analysed by X-ray diffraction (XRD), Scanning electron microscopy (SEM), Brunauer-Emmett-Teller (BET) surface area and Fourier transform infrared spectrophotometer (FTIR). From XRD and FTIR results, it was found that the reaction temperature increases the formation of crystalline phase and morphology of the α-Fe2O3 nanoparticles. Photocatalytic activity of α-Fe2O3 on degradation of methylene blue (MB) was measured under UV-VIS spectrophotometer. The photocatalytic activity of α-Fe2O3 is the highest when α-Fe2O3 synthesized at 160˚C without structure directing agent (Fe2O3-WSDA) was used with MB removal percentage of 14.22 %.